Pengembangan Dapita (Dakon Pintar Matematika) Sebagai Media Pembelajaran Materi Penjumlahan Dan Pengurangan - Salafiyah, Jihan Ainis; Zuliana, Eka; Kuryanto, Mohammad Syaffruddin (PGSD Universitas Muria Kudus, 2024)
The purpose of this study is to determine the results of validation tests, effectiveness test results, and practicality test results of the development of traditional Dapita games (Dakon Pintar Mathematics) as a learning medium for addition and subtraction material for grade II elementary school students. The development of this research uses the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The data used in this study are qualitative data and quantitative data. Data analysis techniques in this study use quantitative descriptive analysis techniques. The validity test in this study uses the Aiken V Index.The validation results obtained on the media aspect are 0.940741 are included in the very valid category. The validation results obtained on the material aspect are 0.911111 are included in the very valid category. The effectiveness test in this study used the Mann Whitney and N-Gain tests. Posttest statistical tests in experimental classes with control classes with the Mann Whitney technique obtained Asymp results. Sig. (2-tailed) 0.000 0.05 with experimental class mean rank of 31.20 and control class mean rank of 11.29. The results of the experimental class Mann Whitney pretest and posttest showed a pretest mean rank value of 10.90 and a posttest mean rank of 30.10 and the significance showed an Asymp value. Sig. (2-tailed) 0.000 0.05. The results of pretest and posttest tests in the experimental class are known to mean N-Gain value of 0.7894 is included in the high effectiveness category. The results of the pretest and posttest N-Gain tests in the control class are known to mean N-Gain values of 0.3387 included in the medium effectiveness category. The practicality test of Dapita learning media (Dakon Pintar Mathematics) obtained a score with a presentation of 95% in the very practical category